Determination of solvation free energy of carbon dioxide (CO2) in the mixture of brine, Alfa Olefin Sulfonate (AOS) and CH4 after foam fracturing in the shale reservoirs on enhanced shale gas recovery (ESGR) - Qi, C.L. (Elsevier B.V., 2018)
Fracturing in the form of foam fracturing is often involved in dealing with the exploitation of unconventional shale resources. On the other hand, Molecular Dynamics (MD) simulation has been developed progressively in the recent decades to provide the temporal and the spatial resolutions, which are experimentally unavailable. The MD simulation considers the atomic and the molecular interactions at microscopic and macroscopic levels. The objective of this research is to improve fluid interaction during hydraulic fracturing of the shale gas reservoirs. The potential parameters include the high reservoir pressure and high temperature (HPHT), the concentration of the surfactant, the presence of carbon dioxide (CO2), and the brine salinity. The simulation focuses on the post effect of hydraulic fracturing on the shale system after the fracturing process has had taken place whereby the CO2 is introduced into the shale gas system, which consists of methane (CH4) with brine and surfactants applied during the foam fracturing is Alfa Olefin Sulfonate (AOS). Different brine salinity, temperature, and pressure are varied in the simulation to determine the most spontaneous combination for the reservoir condition for the solvation of CO2 in the shale fluid system in the reflection of solvation free energy. The simulation result is validated with the experimental study, which is performed to determine the critical micelle concentration (CMC) value of AOS solution in the two-phase fluid consisting of CO2 and brine. The result shows that the most spontaneous system happens at the condition of 423.15 K and 30,000 ppm salinity. The pressure is fairly insignificant to the output of solvation free energy. The larger the negativity of the solvation free energy indicates that the more spontaneous of the CO2 in the interaction with the surrounding particles in the system. This research is beneficial in the future prediction of the behavior and the spontaneity of the CO2 in the shale gas recovery. Apart from that, the CMC in simulation and experimental results are 0.014 wt and 0.016 wt which proves that the simulation result is valid. Â© 2018 Elsevier B.V.